2002
DOI: 10.1007/s004240100705
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular pH in rat renal inner medullary thin limbs of Henle’s loop

Abstract: Regulation of intracellular pH (pHi) was studied in isolated rat renal inner medullary thin limbs of Henle's loop in bicarbonate/phosphate-buffered medium with high pCO2, high osmolality ( congruent with670 mosmol/kg H2O; 270 mM urea; 180 mM NaCl), organic osmolytes, and a pH of 6.8 to approximate the physiological in vivo environment. The pH-sensitive fluorescent dye 2',7'-bis(2-carboxyethyl)-5,6-carboxyfluorescein (BCECF) was used to measure pHi. Resting pHi was always acid and significantly more acid in des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…As expected, expression was stronger in renal medulla than in cortex (Figures 4 and 6). This is in line with the current literature [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…As expected, expression was stronger in renal medulla than in cortex (Figures 4 and 6). This is in line with the current literature [28,29].…”
Section: Discussionsupporting
confidence: 89%
“…A previous study on the renal inner medulla tLH has been demonstrated to express NHE1, NHE3, and H,K-ATPase [24]. The present study is the first to delineate that aldosterone could rapidly elevate the pEGFR-pERK1/2 cascade in this segment of the rat kidney.…”
Section: Discussionmentioning
confidence: 54%
“…Both apical and basolateral membranes were labeled. A bafilomycin-sensitive vacuolar H ϩ -ATPase has also been detected by functional measurements in this initial segment (407). No other segments of long or short thin limbs have been reported to contain the vacuolar H ϩ -ATPase.…”
Section: B Loop Of Henlementioning
confidence: 61%